Iconografía de la idea de España en los manuales escolares durante la transición a la democracia (1976-1983) - CAMPOS PÉREZ, Lara (Cuadernos de Historia Contemporánea, 2010)
In this article I analyze the iconographic construction of the idea of nation in Spain Turing the country’s transitional period. The analysis is based on images (pictures and photographs) related to the nation concept, which were included in elementary school’s History, Civic Education and Patriotic Education books. This study aims to be an approach to the different ways in which the notion of Spain was conceived by the equally different political actors who took part in the production of these books (political parties and the Catholic Church, mainly) and, therefore, to the way it was represented by a series of images, which were expected to show the values and the historical justification of this idea.